PENGARUH PEMBERIAN JENIS FESES TERNAK BERBEDA TERHADAP PERTUMBUHAN RUMPUT BB BIOGEN - Fatimah, Nurul; Amrullah, Amrullah; Yani, Ahmad; Budiman, Cecep; Hamdani, Asrul; Wahyu Satria, Edi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Biogen BB grass is a superior variety used as forage, particularly for cattle, goats, and sheep, due to its high potential for increasing productivity and feed quality. This study aimed to determine the effect of different types of livestock manure on the growth of Biogen BB grass. The study was conducted from January to March 2026 using a randomized block design with four treatments and four groups. Data were analyzed using analysis of variance for plant height, leaf length, leaf width, stem diameter, and number of tillers. The results showed that the highest average values ​​for all variables, such as plant height, ranged from 21.16 to 26.89 cm per two weeks, leaf length from 16.70 to 25.05 cm per two weeks, leaf width from 5.70 to 7.00 cm per two weeks, stem diameter from 4.07 to 8.59 cm per two weeks, and number of tillers from 1.08 to 1.54 cm per two weeks.